Determinants of Profitability in Life and Non-Life Insurance Sector of Pakistan: An Endogenous and Exogenous Evaluation - Rahman, Shams Ur; Jan, Muhammad Farooq; Iqbal, Khursheed (JISR management and social sciences & economics, 2018)
The study is designed to identify the determinants of profitability in the insurance industry of Pakistan. The panel data set of 41 insurance companies (life, non-life, and takaful insurance) from 2007-2017 was employed. Hausman’s specification and Breusch-Pagan Lagrange multiplier (LM) tests have selected the most appropriate test i.e. fixed effect and pooled OLS model for this study. The results of pooled OLS and fixed effect model reveal that insurancespecific and macroeconomic factor like leverage, business risk, and inflation rate are negative but significantly affect the profitability of the insurance sector. However, size and GDP rate has a positive and statistically significant influence on profitability. Liquidity and growth are insignificant determinants of the study. This is the first study that covers the entire insurance industry, which is also composed of the takaful industry, along with firm-specific and country-specific attributes and applies the most suitable models for the study. Thus, this study is very important for top-echelon and policy- makers of the insurance sector of Pakistan regarding the profitability of the firm and wealth of the shareholders.